Toll-like receptor mRNA levels in alveolar macrophages after inhalation of endotoxin - Maris, N A; Dessing, M C; de Vos, A F; Bresser, P; van der Zee, J S; Jansen, H M; Spek, C A; van der Poll, T (The European respiratory journal, 2006)
Toll-like receptors (TLRs) are pattern-recognition receptors that have been implicated in the initiation of innate immune responses upon the first encounter with invading pathogens. The airways are frequently exposed to various types of lipopolysaccharide (LPS) from the environment or from pathogens. The current study was designed to determine the effect of LPS on TLR gene expression in human alveolar macrophages in vivo. In total, 16 healthy subjects were enrolled in a single-blinded, placebo-controlled study. Subjects inhaled 100 microg LPS or normal saline (n = 8 per group). Measurements were performed in alveolar macrophages purified from bronchoalveolar lavage fluid obtained 6 h post-challenge. Inhalation of LPS by healthy human volunteers resulted in enhanced alveolar macrophage expression of mRNAs encoding TLRs 1, 2, 7, 8 and CD14, and reduced expression of mRNAs encoding TLR4 and lymphocyte antigen 96. In conclusion, lipopolysaccharide differentially influences the toll-like receptor mRNA expression profile in human alveolar macrophages in vivo.